SERS chemical enhancement of 2,4,5-trichlorophenoxyacetic acid absorbed on Au20, its Au-Ag and Au-Cu bimetallic clusters: a DFT study - Le, Thi Thuy Huong; Truong, Dinh Hieu; Nguyen, Thi Le Anh; Pham Minh Quan,; Ngo, Thi Chinh; Duy Quang, Dao (Vietnam Journal of Science and Technology, 2022)
The surface-enhanced Raman scattering (SERS) phenomenon of 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) adsorbed on Au20 pyramidal cluster is studied by Density Functional Theory. All possible adsorption configurations between the adsorbate and the Au20 clusters are evaluated and the vibrational assignments of normal Raman and SERS spectra are analyzed. The result shows that the most stable adsorption configuration of the adsorbate on Au20 cluster is formed by the interaction of O13 (-COOH group) and Au atom. The SERS activities of 2,4,5-T adsorbed on 1:1 Au-Ag and Au-Cu bimetallic clusters are also investigated. For bimetallic clusters, the substitution of 1, 4 or 10 Au atoms by Ag/Cu is performed by replacing the respective number of Ag/Cu atoms in 1, 2 and 3 parallel layers of the Au20 cluster. While the Raman scattering activity of the Au10Ag10 cluster is comparable to that of the Au20 cluster, it is remarkably higher than the Au10Cu10 cluster. This observation is explained by the molecule-to-cluster charge transfer process. The obtained results are hoped to contribute to better design of SERS-based analytical sensors for mobile and on-site applications.